Youth in residential care: A cross-sectional mediation analysis of youth’s perceptions of their social images, self-representations, and adjustment outcomes - Calheiros, M. M. (2021)
Individuals’ perceptions of their social images [i.e., meta-representations (MR)] and perceived stereotyping threat create involuntary stress responses that may affect important outcomes, such as self-esteem, academic achievement, and mental health. This study aimed to (1) analyze the indirect associations between residential care youth’s MR and their psychological adjustment (i.e., externalizing and internalizing problems) through their self-representations (SR) and (2) test the moderating role of youth’s age and residential unit size in those associations. A sample of 926 youth aged between 12 and 25years old filled out self-report questionnaires regarding their representations about how people in general perceive them (i.e., MR) and their SR. Residential care professionals filled in the socio-demographic questionnaires and the Child Behavior Checklist. Data were analyzed through multiple mediation models and moderated mediation models. Results showed that (1) youth’s behavioral MR were indirectly associated with higher internalizing and externalizing behavior through higher levels of behavioral SR and (2) youth’s emotional MR were associated with higher internalizing problems through higher emotional SR, but also with lower internalizing problems through lower levels of behavioral SR. These results emphasize the importance of stimulating positive SR, by showing that they can be a protective factor for youth in residential care.